Serologic Markers for Ebolavirus Among Healthcare Workers in the Democratic Republic of the Congo. (19th September 2018) - Hoff, Nicole A; Mukadi, Patrick; Doshi, Reena H; Bramble, Matthew S; Lu, Kai; Gadoth, Adva; Sinai, Cyrus; Spencer, D'Andre; Nicholson, Bradley P; Williams, Russell; Mossoko, Matthias; Ilunga-Kebela, Benoit; et al.
Abstract : Healthcare workers in an area with a previous Ebola outbreak in the Democratic Republic of the Congo exhibited both antibody response and neutralizing capacity to at least 1 Ebola protein, despite never having been diagnosed with Ebola virus disease. Abstract: Healthcare settings have played a major role in propagation of Ebola virus (EBOV) outbreaks. Healthcare workers (HCWs) have elevated risk of contact with EBOV-infected patients, particularly if safety precautions are not rigorously practiced. We conducted a serosurvey to determine seroprevalence against multiple EBOV antigens among HCWs of Boende Health Zone, Democratic Republic of the Congo, the site of a 2014 EBOV outbreak. Interviews and specimens were collected from 565 consenting HCWs. Overall, 234 (41.4%) of enrolled HCWs were reactive to at least 1 EBOV protein: 159 (28.1%) were seroreactive for anti-glycoprotein immunoglobulin G (IgG), 89 (15.8%) were seroreactive for anti-nucleoprotein IgG, and 54 (9.5%) were VP40 positive. Additionally, sera from 16 (2.8%) HCWs demonstrated neutralization capacity. These data demonstrate that a significant proportion of HCWs have the ability to neutralize virus, despite never having developed Ebola virus disease symptoms, highlighting an important and poorly documented aspect of EBOV infection and progression.